Studi Diskriptif Pengguna Metode Kontrasepsi Modern - Wiwin Hindriyawati; Tatik Tatik; Reni Tri Lestari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Family planning program is also specifically designed to create progress, stability, and economic, social, and spiritual prosperity for every resident. The family planning program in Indonesia is regulated in Law No. 10 of 1992. The prevalence of contraceptive use among women aged 15-49 years with marital status is 59.3% using modern methods (Implant, MOW, MOP, IUD, Condoms, Pills), 0.4 % used traditional contraception (MAL/Breastfeeding, Periodic/calendar abstinence, interrupted intercourse, others), 24.7% had ever done family planning, and 15.5% had never done family planning. Method research uses Descriptive observational method using cross sectional design, sampling with total sampling technique. The sample of this research is couples of childbearing age who use modern contraception as many as 249 respondents, by collecting secondary data. The results of the descriptive statistical test showed that most of the respondents were aged > 35 years, 152 (61.0%), the largest respondent's education was high school education 102 (42%), the largest respondent's occupation was as a casual worker as many as 80 (12.0%), the largest parity was in the number of living children 2 were 126 (50.6%), the most used contraceptive method was the Non-MKJP method 193 (77.5%), with the largest injection contraception 160 (64.3%). In conclusion, most of the respondents are >35 years old, with high school education, type of casual work, most parity has 2 living children, non-MKJP contraceptive users with injection dominant contraception.Keywords: Age, Education, Occupation, Parity, Modern Contraceptive Methods